Dopamine triggers TOR signaling cascade to drive biomass and astaxanthin hyperaccumulation in Haematococcus lacustris under coordinated salinity and gradient light stress - Shiyu Lin; Qingwei Wang; Raoqiong Che; Qingqing Li; Chunli Yu; Min Yang; Lifang Li; Penghua Gao; Ying Qi; Feiyan Huang; Xiang Wang; Yongteng Zhao; et al. (Bioresource Technology, 2026)

Enzymatic synthesis and structural characterization of Sn-2 α-linolenic acid-enriched structured lipids from cottonseed oil via 13C NMR and UPLC-MS/MS - Shiyang Yu; Shiyu Yu; Hexi Yuan; Yanhong Lin; Changqing Wei; Peng Luo (Food Research International, 2026)

Advances in selenium-containing brown rice protein: structural characteristics, functional modification, and applications - Shu Li; Xinjie Shang; Yaxin Wu; Yumeng Wang; Shiyu Lin; Zexu Li; Zhaohui Xu; Yixuan Li; Yao Tang; Rui Yang (Food Hydrocolloids, 2026)

Overlooked effects of common alcohol quenching agents on electron transfer pathway in persulfate activation system - Xuerong Zhou; Lin Zhang; Shiyu Liu; Huchuan Yan; Dengsheng Ma; Qihong Yang; Bing Ding; Cui Lai; Ming Yan; Zizhu Peng (Chemical Engineering Journal, 2026)

Printable aligned carbon fiber-reinforced polylactic acid composites towards tunable thermal management and mechanical performance - Jiajun Yu; Liping Gong; Purun Wang; Shilong Duan; Qiankun Chen; Shiyu Lin; Zimu Li; Weihua Li; Shuai Liu (Chemical Engineering Journal, 2026)

An injectable thiolated alginate/oxidized dextran hydrogel with curcumin-copper nanoparticles for corneal neovascularization after alkali burn - Zhongwu Bei; Lin Ye; Shiyu Liang; Qi Tong; Xicheng Li; Jianan Li; Xiaorui Yu; Yujia Wei; Xuyue Liang; Tingyu Yang; Yun Yang; Longqian Liu; et al. (Carbohydrate Polymers, 2026)

Reclamation to aquaculture ponds accelerates losses of Fe-bound organic carbon in estuarine wetlands - Junma Chen; Liwen Cheng; Yunying Fang; Ji Chen; Weiqi Wang; Yi Zheng; Shiyu Chen; Lin Wang; Jordi Sardans (Water Research, 2026)

CsMYB6 promotes crocins biosynthesis in response to JA signaling in Crocus sativus L - Shiyu Wang; Chuyu Lin; Xingyun Shi; Aicun Zhou; Ting Chen; Ying Zheng; Qingsong Shao; Lei Zhang; Lan Ding; Bingcong Xing (Journal of Plant Physiology, 2026)

Superhydrophobic felt with photo/electrothermal conversion for antibacterial activity, oil-water separation and anti-icing/de-icing performance - Saiyu Zhou; Siyu Wu; Minghao Pan; Shiyu Hua; Peijin Wu; Ziyu Zhao; Liwei Lin (Process Safety and Environmental Protection, 2026)

Enhancing microalgal bioremediation and bioproduction with chemical additives: Mechanisms and strategic perspectives - Yongteng Zhao; Shiyu Lin; Qingqing Li; Feiyan Huang; Xiang Wang; Lei Zhang; Xuya Yu; Lei Yu (Algal Research, 2026)

Pre- and Syn-Mineralization Fracture Patterns in the Sanshandao and Jiaojia Fault Zones and Their Controls on the Distribution of Gold Orebodies: Insights from Numerical Simulations - Chuan Xu; Lin Yang; Qingfei Wang; Shiyu Zhao; Huajian Li; Zhengjiang Ding; Dapeng Li; Zhao Liu (Natural Resources Research, 2026)

Osteopontin as an emerging multifunctional food ingredient: recent advancements, production, applications, and challenges - Shiyu Lin; Xiuxiu Teng; Xinjie Shang; Shu Li; Jingjing Xu; Yao Tang; Rui Yang (Critical Reviews in Food Science and Nutrition, 2026)

Genomic and Phenotypic Characterization of the Probiotic Potential and Safety of Bacillus velezensis CH3-2 Isolated from Chahua Chicken - Le Xu; Shang Wang; Shiyu Chen; Chen Liu; Haiyue Wu; Qinghua Liu; Minjie Hu; Qiuye Lin; Zhenhui Cao (Probiotics and Antimicrobial Proteins, 2026)

Corrigendum to “Multi-task deep convolutional neural network for weed detection and navigation path extraction” [Comput. Electron. Agric. 229 (2025) 109776] - Yongda Lin; Lingxiao Wang; Shiyu Xia; Baiyu Qiao; Hu Han; Linhui Wang; Xiongkui He; Yajia Liu (Computers and Electronics in Agriculture, 2026)

A novel Curcuma wenyujin-derived fructan modulates gut microbiota and metabolic pathways to ameliorate DSS-induced colitis - Zijun Li; Zhen Li; Liuxi Chu; Shiyu Hu; Chang Xue; Huixin Lin; Yawen Luo; Yihui Zhang; Jian Zhang; Zhouguang Wang (Carbohydrate Polymers, 2026)

Sustainable multifunctional packaging films based on chitosan and food waste-derived carbon nanodots for fruit preservation - Ying Ren; Dan Chen; Shiyu Lin; Xiaoping Fan; Liming Cao (Journal of Food Engineering, 2026)

Effect of Limosilactobacillus reuteri SBC5-3 Cell-free Supernatant on Growth Performance, Intestinal Inflammation, and Microbiota in Weaned Piglets Challenged With Enterotoxigenic Escherichia coli K88 - Le Xu; Guoying Bao; Shiyu Chen; Chen Liu; Xiannian Zi; Minjie Hu; Qinghua Liu; Qiuye Lin; Zhenhui Cao (Probiotics and Antimicrobial Proteins, 2026)

Research on the application of nanopore sequencing technology in investigating microbial data deviation - Xiaoling Zheng; Hongxia Yang; Wanzi Gong; Shiyu Wang; Yinhuan Wang; Deyin Deng; Tingzhang Wang; Hong Li; Chenshui Lin (Antonie van Leeuwenhoek, 2026)

Spurious seasonality in satellite turbidity monitoring driven by K1 tidal aliasing - Shiyi Cao; Qian Yu; Shiyu Zhang; Jie Feng; Yidong Guo; Hangjie Lin; Yunwei Wang (Remote Sensing Applications: Society and Environment, 2026)

Origin, evolution and precipitation mechanism of ore-forming fluids in Jiaojia belt, Jiaodong Peninsula: Insights from trace elements and S Fe isotopes of pyrite - Jinyu Cheng; Lin Yang; Qingfei Wang; Yixin Li; Wen Zhang; Bin Sun; Xue Dong; Shiyu Zhao; Dapeng Li; Kexin Zhao; Hong Wang (Journal of Geochemical Exploration, 2026)

Phosphorus-driven enhancement of microalgal growth, lipid biosynthesis, and nutrient removal efficiency in Monoraphidium sp. QLZ-3: Implications for biofuel production and high‑phosphorus wastewater treatment - Shiyu Lin; Jinkun You; Yongteng Zhao; Qingwei Wang; Ying Qi; Feiyan Huang; Xuya Yu; Lei Yu (Algal Research, 2026)

Cottonseed protein as a sustainable alternative plant protein: Basic characteristics, recent advancements, applications and limitations - Xinjie Shang; Shu Li; Shiyu Lin; Shihao Sun; Li Liang; Yuyu Zhang; Rui Yang (Trends in Food Science & Technology, 2026)

From farm to table: The statuses, hotspots, and trends on research of HACCP application in global food supply chains (1990–2025)—A bibliometric analysis based on CiteSpace - Jiuhao Chen; Junfei Chen; Yuze Guan; Shijie Xue; Yinqiang Liu; Yifan Guo; Shisheng Zhu; Shiyu Quan; Tianci Lin; Zhihao Ni (Food Control, 2026)

Provincial employment effects of coal mine retirement in China's carbon-neutral transition - Shiyu Li; Zanfeng Wang; Wenji Zhou; Anlan Lin; Hongtao Ren (Energy Policy, 2026)

Periosteum-inspired lightweight aerogel composite for ultrahigh energy dissipation and dynamic impact perception - Qiankun Chen; Jianpeng Wu; Shuai Liu; Xinyi Wang; Shiyu Lin; Purun Wang; Xinglong Gong; Shaolin Ge; Ken Cham-Fai Leung; Shouhu Xuan (Chemical Engineering Journal, 2026)

Water-Quenched Slag and Desulfurization Gypsum Low-Alkali Chemical Solidification of Copper-Contaminated Soil: Mechanical Properties, Leaching Toxicity, and Solidification Mechanisms - Zhenhua Wang; Guolun Hou; Lin Guo; Dongli Zuo; Jun Xu; Jiayue Yuan; Shiyu Chen (Water, Air, & Soil Pollution, 2026)

Assessing the Probiotic Properties and safety of Limosilactobacillus reuteri LP4 Isolated from Apis cerana Based on Whole Genome and Phenotype Analyses - Le Xu; Pingping Fang; Mingkui Lv; Shiyu Chen; Chen Liu; Sifan Wang; Jiqin Li; Kun Dong; Qiuye Lin; Zhenhui Cao (Probiotics and Antimicrobial Proteins, 2026)

Green Synthesis of Nitrogen-Doped Carbon Quantum Dots from Medium-Molecular-Weight Chitosan for Ultrasensitive Fe³⁺ Detection and Responsive Probe - Lulu Feng; Hainan Li; Zishuai Zhang; Shuang Pang; Zhiyu Liu; Jiahao Lin; Shiyu Wang; Zhenning Lou (Journal of Fluorescence, 2026)

Methyl group donor‑resolved isotopic diagnostics reveal mechanistic diversity in UV‑driven methylation of Hg(II) - Lin Yang; Kun Zhang; Maojun Yu; Shiyu Li; Deming Han; Ben Yu; Cailing Xiao; Ligang Hu; Yongguang Yin; Jianbo Shi; Guibin Jiang (Journal of Hazardous Materials, 2026)

Biomimetic hetero-multilayer insulation films with advanced thermal conductivity and mechanical performance - Shiyu Lin; Jianpeng Wu; Yu Wang; Qiankun Chen; Purun Wang; Jiajun Yu; Yuan Yuan; Junshuo Zhang; Xinglong Gong (Chemical Engineering Journal, 2026)

Oven-drying of cellulose 3D skeleton for solar-powered seawater desalination with the assistance of cell template strategy - Lin Tang; Shiyu Zong; Jingxuan Ai; Xinyan He; Jiufang Duan; Jianxin Jiang (Carbohydrate Polymers, 2026)

Lithium ions protected orbital symmetry enables reversible oxygen redox in layered manganese-based cathodes - Ang Gao; Shiguang Zhang; Xiaohui Rong; Qinghua Zhang; Ting Lin; Yichi Wang; Yujie Chen; Valentina A. Bocharova; Weiguang Lin; Shiyu Wang; Pengxiang Ji; Hongwei Li; et al. (Science Bulletin, 2026)

Advancing Non‐Contact Fish Phenotyping via Optical Sensing: Toward Precision Aquaculture - Kai Lin; Shiyu Zhang; Wei Wang; Tian Dong; Wen Ding; Chenfan Geng; Yihang Lu; Hongxia Hu (Reviews in Aquaculture, 2026)
Non‐contact fish phenotyping has become an essential strategy for precision aquaculture, enabling accurate, high‐throughput, and non‐invasive trait measurement. In this review, a digital phenotyping framework is summarized, including application‐driven trait definition, multimodal data acquisition (2D, 2.5D, and 3D imaging), and automated phenotypic analysis based on computer vision and deep learning. According to current research paradigms, optical phenotyping applications are systematically categorized into three major domains: morphological, behavioral, and appearance‐based phenotyping. Multimodal optical sensing systems now support high‐throughput morphological, behavioral, and appearance‐based phenotyping, enabling applications ranging from biomass estimation and intelligent feeding control to selective breeding, product quality evaluation, species identification, and disease diagnosis. Despite rapid methodological progress, most existing studies remain confined to laboratory or semi‐controlled environments, and large‐scale implementation in commercial production systems is still limited. Key challenges persist in underwater image degradation, posture‐induced measurement uncertainty, data heterogeneity, model generalizability, computational constraints, and the integration of phenotypic and genomic data for precision breeding. Finally, future development pathways are discussed, including efficient and flexible data acquisition platforms, lightweight and real‐time processing, transfer and few‐shot learning, multimodal data fusion, novel phenotype quantification, and standardized open datasets. Based on a comprehensive analysis of over 100 studies, this review maps the current technological landscape and proposes pathways toward scalable, intelligent phenotyping systems that can improve fish welfare, enhance breeding efficiency, and promote sustainable aquaculture management.

Low-altitude remote sensing and deep learning-based canopy detection method for the navigation of orchard unmanned ground vehicles - Yongda Lin; Xiaofei Song; Weiming Xiao; Dongdong Kuang; Shiyu Xia; Honggen Chang; Supakorn Wongsuk; Xiongkui He; Yajia Liu (Computers and Electronics in Agriculture, 2025)

CHAPS-involved chitooligosaccharide glycosylation of ferritin cage for encapsulation of bioactive molecule by a mild process - Junrui Ma; Runxuan Chen; Chang Liu; Shiyu Lin; Chunkai Gu; Lingling Zhang; Ruge Cao; Fang Wang; Demei Meng; Shihao Sun; Yuyu Zhang; Rui Yang (Food Chemistry, 2025)

Bio-templated nanocellulose/ZnO hybrids reinforced PVA/chitosan films with synergistic antibacterial activity for enhanced food preservation - Dan Chen; Shiyu Lin; Liming Cao; Wei Huang (Food Packaging and Shelf Life, 2025)

Low-temperature heat recovery: An economic approach to renovate air-impaired LiNbOCl4 electrolyte for boosted stability in high-performance all-solid-state batteries - Lin Li; Shiyu Liu; Siwu Li; Ziling Jiang; Qiyue Luo; Ziyu Lu; Miao Deng; Wenqian Tian; Jie Yang; Chen Liu; Qiao Wang; Chuang Yu (Chemical Engineering Journal, 2025)

Electrostatic and functional group-mediated biosorption of microalgae and lead using biosafe Aspergillus oryzae 3.042 fungal pellets - Feili Li; Shiyu Chen; Yijie Lin; Jingjing Fang; Wen Shi; Junjie Qian; Gaoxiang Zhang; Jun Hu (Bioresource Technology, 2025)

Comprehensive multi-omics analysis of nucleotide metabolism: elucidating the role and prognostic significance of UCK2 in bladder cancer - Yadong Guo; Ziyou Lin; Wentao Zhang; Haotian Chen; Yuxin Chen; Yongqiang Liu; Zezhi Shan; Shiyu Mao; Xudong Yao (Functional & Integrative Genomics, 2025)

Spatio-temporal heterogeneity of the estuarine turbidity maximum retreat in the Changjiang river estuary under reduced sediment supply - Jie Feng; Qian Yu; Shiyi Cao; Shiyu Zhang; Tianxu Ni; Zhiyun Du; Hangjie Lin; Yunwei Wang; Ya Ping Wang (Geo-Marine Letters, 2025)

Evaluation of soybean protein peptides on growth, antioxidative capacity, non-specific immunity, and disease resistance for juvenile Litopenaeus vannamei - Huaxing Lin; Shuqing He; Yuanming Yi; Xiaomin Zhang; Shiyu Kou; Qihui Yang; Beiping Tan; Shuyan Chi (Animal Feed Science and Technology, 2025)

Associations between element mixtures and biomarkers of pathophysiologic pathways related to autism spectrum disorder - Shiyu Zhang; Hao Zhou; Junfeng (Jim) Zhang; Tianqi Wang; Yanbo Teng; Peng-Chou Tsai; Christine Ladd-Acosta; Yan Lin; Yi Wang (Journal of Trace Elements in Medicine and Biology, 2025)

Mechanistic insights into H2O2 activation by high-density iron single-atom catalysts for efficient water treatment: Surface-bound radical and singlet oxygen - Fuhang Xu; Cui Lai; Mingming Zhang; Zuying Yao; Dengsheng Ma; Bisheng Li; Meng Qin; Huchuan Yan; Xiuqin Huo; Xing Fan; Biting Wang; Shiyu Liu; et al. (Journal of Environmental Chemical Engineering, 2025)

Fluid source and evolution in Jinchang Au-Ni superimposed deposit, Ailaoshan, southeastern Tibet - Shiyu Liu; Huajian Li; Mengdi Lu; Ziqing Zhu; Haoying Chen; Chaoyi Dong; Lin Yang; Wei Ma (Journal of Asian Earth Sciences, 2025)

Improving soy sauce quality via co-fermentation with indigenous Tetragenococcus: Reducing biogenic amines and enhancing flavor - Shiyu Wu; Zhenxiao Sun; Jian Guo; Dongmei Li; Xinping Lin; Sufang Zhang; Chaofan Ji (Food Research International, 2025)

Peroxydisulfate activation by copper metal-organic framework derivatives: Deciphering the role of copper species - Shiyu Liu; Cui Lai; Lei Qin; Dengsheng Ma; Xuerong Zhou; Huchuan Yan; Fuhang Xu; Lin Tang; Xingzhong Yuan (Environmental Research, 2025)

Oxygen vacancy-assisted CuCo tandem catalyst boosts efficient electrocatalytic neutral ultralow-concentration nitrate to ammonia - Xing Fan; Cui Lai; Lei Qin; Mingming Zhang; Huchuan Yan; Shiyu Liu; Dengsheng Ma; Qianting Liu; Lin Tang (Chemical Engineering Journal, 2025)

Ion/electron/stress-triple-regulated Li deposition via multifunctional bismuth species in sulfide-based all-solid-state lithium metal batteries - Ziling Jiang; Siwu Li; Wenwen Hu; Shiyu Liu; Lin Li; Jie Yang; Miao Deng; Ziyu Lu; Xinxin Wang; Qin Chen; Hui Yang; Chen Liu; et al. (Chemical Engineering Journal, 2025)

Strength Deterioration Characteristics of Soft and Hard Interbedded Rock Masses in Three Gorges Reservoir Area Induced by Wetting-Drying Cycles - Qiong Wu; Di Wang; Huiming Tang; Jintao Kang; Hongming Luo; Yuxin Liu; Shiyu Li; Bo Zhang; Zhiqi Liu; Zhiwei Lin (Journal of Earth Science, 2025)

Hydrodynamic processes and extreme events recognized from the sedimentary records at ancient Port Shuomen in the Oujiang River mouth, Southeast China - Xin Wei; Yanhua Liang; Tuanhui Liu; Zhihang Ma; Xiaolin Ma; Shiyu Ji; Fangyou Lin; Hao Xu; Zhanghua Wang (王张华) (Marine Geology, 2025)

Enhancing soil carbon sequestration in jasmine gardens: Differential effects of straw and biochar on mineral-associated and particulate organic carbon - Xiaoying Ren; Wenwen Yang; Liping Ye; Siyan Lin; Yuan Li; Weiqi Wang; Jordi Sardans; Junma Chen; Shiyu Chen; Siqi Yu; Li Hou; Akash Tariq; et al. (Journal of Environmental Management, 2025)

Unveiling the components, physiological functions and emerging trends of hydroxycinnamic acid amides in goji berry (Lycium) - Siyuan Wei; Yuying Wang; Shiyu Zhou; Shina Luo; Yunuo Lin; Ruixi Wang; Qinyue Jia; Tingting Feng; Guoping Zhao; Xuefeng Yin; Fangwei Yang (Food Research International, 2025)

Effects of DpWRI1-like gene overexpression in transgenic Dunaliella parva - Lingru Ruan; Juying Lin; Lina Wu; Yanyan Liang; Xiumin Zhang; Shiyu Liang; Limei Huang; Changhua Shang (Antonie van Leeuwenhoek, 2025)

Comprehensive analysis of microplastics at typical outlets around Hainan Island: From spatial distribution to flux estimation and correlation analysis - Shiyu Xie; Yuanyuan Su; Dan Qi; Fei Liu; Liu Gao; Ruiqi Bao; Xing Cheng; Xubing Lin; Tingting Zhang; Licheng Peng (Water Research, 2025)

Growth history of garnet from the Dulong Sn-Zn-In polymetallic deposit: Geochemical and U Pb age constraints and their metallogenic significance - Shiyu Liu; Lin Ye; Yuping Liu; Hansheng Long; Chen Wei; Zhenzhong Xiang (Journal of Geochemical Exploration, 2025)

Lifetime exposure to health-related air pollutants in the United Kingdom: A spatiotemporal evaluation (1930–2010) through WRF-CMAQ modeling - Ge Chen; Yiming Liu; Haofan Wang; Menghe Wang; Lan Chen; Hejun Hu; Shiyu Zhang; Baozhuo Ai; Miao Cai; Zilong Zhang; Qi Fan; Hualiang Lin (Atmospheric Environment, 2025)

Barley young leaf chlorina, a putative pentatricopeptide repeat gene, is essential for chloroplast development in young leaves - Biguang Huang; Daiqing Huang; Jianchun Zhang; Jiwei Xiong; Shiyu Wu; Xinrong Zheng; Likun Huang; Jinbin Lin; Yu Li; Zonglie Hong; J. Allan Feurtado; Weiren Wu (Plant Molecular Biology, 2025)

Revealing future effectiveness of protected areas for biodiversity conservation in the Guangdong-Hong Kong-Macao Greater Bay Area - Fengze Lin; Mingjian Zhu; Xinyi Dong; Shiyu Ling; Bo Luan; Guoliang Pan (Landscape and Urban Planning, 2025)

Efficacy of black soldier fly larvae in converting kitchen waste and the dynamic alterations of their gut microbiome - Le Xu; Qiuye Lin; Shengwen Wang; Shiyu Chen; Rencan Yang; Chen Liu; Qingquan Hu; Zhiyong Zhao; Zhenhui Cao (Journal of Environmental Management, 2025)

Soil phosphorus dynamics and its correlation with ectomycorrhizal fungi following forest conversion in subtropical conifer (Picea asperata) forests - Lixia Wang; Shiyu Song; Huichao Li; Yang Liu; Lin Xu; Han Li; Chengming You; Sining Liu; Hongwei Xu; Bo Tan; Zhenfeng Xu; Li Zhang; et al. (European Journal of Soil Biology, 2025)

Interactive effects of air pollutants and viral exposure on daily influenza hospital visits in Mongolia - Yihui Ge; Yan Lin; Oyu Tsogtbayar; Ser-Od Khuyagaa; Eelin Khurelbaatar; Jargalsaikhan Galsuren; Lauren Prox; Shiyu Zhang; Robert M. Tighe; Gregory C. Gray; Junfeng Zhang; Daramragchaa Ulziimaa; et al. (Environmental Research, 2025)

Removal of single and multi-heavy metals from piggery digestate by the electric field-microalgae system: Influences, kinetics and mechanisms - Xiaosong Tian; Min Wang; Xing Liao; Shiyu Chu; Haixiang Cheng; Xiaoai Lin; Longzao Luo (Algal Research, 2025)

Multi-task deep convolutional neural network for weed detection and navigation path extraction - Yongda Lin; Shiyu Xia; Lingxiao Wang; Baiyu Qiao; Hu Han; Linhui Wang; Xiongkui He; Yajia Liu (Computers and Electronics in Agriculture, 2025)

Inhibition of odor generation during the composting process of fecal sludge from rural toilets by decomposed compost backfilling - Lin Lin; Xingfeng Yang; Yilin Shen; Ping Zhu; Shiyu Niu; Shakib Alghashm; Guoji Ding; Deli Wu; Xiaowei Li (Bioresource Technology Reports, 2025)

Identification and characterization of GRAS genes in passion fruit (Passiflora edulis Sims) revealed their roles in development regulation and stress response - Xinkai Cai; Denglin Li; Chaojia Liu; Jiayi Chen; Xiuqing Wei; Sitong Hu; Lin Lu; Shengzhen Chen; Qinglong Yao; Shiyu Xie; Xiaowen Xu; Ruoyu Liu; et al. (Plant Cell Reports, 2025)

Removal of heavy metals from single- and multi-metal solution by magnetic microalgae-derived biochar - Xiaosong Tian; Shiyu Chu; Yujie Hu; Longzao Luo; Xiaoai Lin; Hui Wang (Journal of Water Process Engineering, 2025)

Biochar addition mitigates asymmetric competition of water and increases yield advantages of maize–alfalfa strip intercropping systems in a semiarid region on the Loess Plateau - Shuai hou; Xingrong Sun; Guohao Chen; Kadambot H.M. Siddique; Zelin Chen; Fu Liu; Shiyu Ping; Hongtao Lai; Hongheng Guo; Yajing An; Zhiling Lin; Zhixin Zhang; et al. (Field Crops Research, 2024)

Method for Non-Contact Measuring the Weight of Sturgeon in Intensive Aquaculture - Junjie Hu; Kai Lin; Shiyu Zhang; Rui Zhang; Hongsong Li; Runqiu Xia (Fishes, 2024)
Weight information plays a pivotal role in sturgeon breeding and production management. However, manual measurement is time consuming and labor intensive due to the immense size of the sturgeon. Due to the unique body shape of the sturgeon, traditional image segmentation algorithms struggle to extract the necessary features from sturgeon images, which makes them unsuitable for this particular species. Moreover, accurately measuring weight in an occlusion environment is difficult. To address these challenges, an improved YOLOv5s model with a context augmentation module, focal-efficient intersection over union, and soft non-maximum suppression was proposed in this paper. To validate the model’s feasibility, the improved YOLOv5s model was first pre-trained using the sturgeon dataset, followed by further training on the occlusion dataset for segmentation tasks. Based on the phenotypic data obtained from the improved model, a multilayer perceptron method was used to estimate the sturgeon’s weight accurately. Experimental results demonstrated that the average precision of the improved YOLOv5s model reached 89.80% under occlusion conditions, and the correlation coefficient of noncontact weight measurement results reached 89.80%. The experimental results showed that the improved algorithm effectively performs segmentation of sturgeon in occlusion conditions and can accurately estimate the mass.

Heterostructured bimetallic MOF-on-MOF architectures on amino-functionalized cellulose for enhanced catalytic water treatment - Yujiao Lin; Wei Zhang; Guangdong Ying; Shiyu Luo; Haisong Wang; Yehan Tao (Journal of Water Process Engineering, 2024)

Transcriptome analysis of Sesuvium portulacastrum L. uncovers key genes and pathways involved in root formation in response to low-temperature stress - Jingyi Yang; Shiyu Lin; Yinghan Shen; Jingtao Ye; Xiamin Jiang; Sheng Li; Maowang Jiang (Plant Molecular Biology, 2024)

A remote-controlled portable workstation for highly sensitive and real-time chemiluminescent detection of cadmium - Shiyu Zeng; Haoyu Zhu; A.S.M. Muhtasim Fuad Sohan; Jun Liu; Xinhua Wan; Xiaodong Lin; Binfeng Yin (Food Chemistry, 2024)

Integrated transcriptomic and metabolomic analyses revealed the effect of melatonin on delaying persimmon fruit softening - Yuwei Wang; Shiyu Lin; Mengyuan Zhang; Jiaojiao Nie; Aijun Tang; Ningjing Sun; Shuyu Zeng; Xiaofen Liu; Yuduan Ding; Xueren Yin; Qinggang Zhu (Postharvest Biology and Technology, 2024)

Effects of light quality on the growth, productivity, fucoxanthin accumulation, and fatty acid composition of Thalassiosira pseudonana - Maoyingzang Peng; Shiyu Lin; Yinghan Shen; Ruibing Peng; Sheng Li; Xiamin Jiang; Maowang Jiang (Journal of Applied Phycology, 2024)

Inhibitory effect of ammonium conversion by deep nitrogen application effectively reduces gaseous nitrogen losses - Changhong Liu; Yanjie Qu; Changjie Feng; Yongqiao Zhang; Shiyu Li; Zhenhua Lei; Haowei Feng; Xiang Lin; Dong Wang (Agriculture, Ecosystems & Environment, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

Identification of Key Factors in Cartilage Tissue During the Progression of Osteoarthritis Using a Non-targeted Metabolomics Strategy - Shiyu Sun; Minghui Chen; Tingting Zhang; Yanyan Wang; Weijun Shen; Tao Zhang; Jian Liu; Haidan Lan; Jianyuan Zhao; Fuqing Lin; Xuan Zhao (Phenomics, 2024)
This research was to reveal the key factors in the progression of osteoarthritis (OA) using non-targeted metabolomics and to find targeted therapies for patients with OA. Twenty-two patients with knee OA scheduled for total knee arthroplasty were divided into two groups: Kellgren–Lawrence (KL) grade 3 ( n = 16) and grade 4 ( n = 6), according to plain X-rays of the knee. After the operation, the cartilages of femur samples were analyzed using non-targeted metabolomics. When compared with grade 3 patients, the levels of choline, 2-propylpiperidine, rhamnose, and monomethyl glutaric acid were higher; while 1-methylhistamine, sphingomyelin (SM) (d18:1/14:0), zeranol, 3- (4-hydroxyphenyl)-1-propanol, 5-aminopentanamide, dihydrouracil, 2-hydroxypyridine, and 3-amino-2-piperidone were lower in grade 4 patients. Furthermore, some metabolic pathways were found to be significantly different in two groups such as the pantothenate and coenzyme A (CoA) biosynthesis pathway, the glycerophospholipid metabolism pathway, histidine metabolism pathway, lysine degradation pathway, glycine, serine and threonine metabolism pathway, fructose and mannose metabolism pathway, the pyrimidine metabolism pathway, and beta-alanine metabolism pathway. This work used non-targeted metabolomics and screened out differential metabolites and metabolic pathways, providing a reliable theoretical basis for further study of specific markers and their specific pathways in the progression of OA.

Causal association between long-term exposure to air pollution and incident Parkinson’s disease - Baozhuo Ai; Jiayue Zhang; Shiyu Zhang; Ge Chen; Fei Tian; Lan Chen; Haitao Li; Yuming Guo; Angela Jerath; Hualiang Lin; Zilong Zhang (Journal of Hazardous Materials, 2024)

Effects of polypropylene microplastics on carbon dioxide dynamics in intertidal mangrove sediments - Xubing Lin; Shuying Lin; Licheng Peng; Miao Chen; Xing Cheng; Shiyu Xie; Ruiqi Bao; Yuanyuan Su; Tariq Mehmood (Environmental Pollution, 2024)

Quantitative comparison of 2D and 3D monitoring dimensions in fish behavior analysis - Kai Lin; Shiyu Zhang; Junjie Hu; Xingdong Lv; Hongsong Li (Journal of Fish Biology, 2024)
To improve the accuracy and efficiency of fish behavior assessment, this paper focuses on quantitatively exploring the variations and relationships between different monitoring dimensions. A systematic comparison was conducted between 3D and 2D behavioral factors using an infrared tracing system, during both day and night. Significant differences in swimming distance were observed among the different monitoring methods, as determined by two‐way ANOVA and Tukey's test. A correction was applied to account for the disparities observed in 2D swimming distance, ensuring accurate measurements. These findings present a cost‐effective and efficient approach for obtaining precise 3D distance data. Additionally, a kinematic factor called the “number of U‐turns” was proposed to provide a more intuitive characterization of directional changes in fish swimming. Significant differences were observed between 2D and 3D data, with higher percentages of false U‐turn counts and missing U‐turn counts compared to correct counts in the 2D view. These findings suggest that reducing the monitoring dimension may impact the accurate estimation of swimming motion, potentially resulting in inaccurate outcomes. Finally, the statistical analyses of the non‐linear properties of fractal dimension revealed significant differences among the various monitoring methods. This conclusion has practical implications for biologists and physicists, enabling them to improve the accuracy of behavioral phenotyping for organisms exhibiting 3D motion.

Dual-Coordinated atomically dispersed Pt nanozymes evoke efficient pyroptosis for cancer immunotherapy - Jingqi Chen; Yanping Tang; Yan Lin; Xiuxin Lu; Lineng Wei; Shiyu Xia; Wenxin Niu; Weizhong Tang; Weiqing Zhang (Chemical Engineering Journal, 2024)

Ubiquitination-specific protease 7 enhances stemness of hepatocellular carcinoma by stabilizing basic transcription factor 3 - Mingchao Hu; Chengchen Dai; Xieyin Sun; Yinqi Chen; Nuo Xu; Zhaoyi Lin; Shiyu Xu; Chun Cheng; Zhonghua Tan; Saiyan Bian; Wenjie Zheng (Functional & Integrative Genomics, 2024)

The effects of long-term exposure to air pollution on incident mental disorders among patients with prediabetes and diabetes: Findings from a large prospective cohort - Jin Feng; Miao Cai; Zhengmin (Min) Qian; Shiyu Zhang; Yin Yang; Stephen Edward McMillin; Ge Chen; Junjie Hua; Maya Tabet; Chongjian Wang; Xiaojie Wang; Hualiang Lin (Science of The Total Environment, 2023)

Heart valve-inspired self-lubricating anticoagulant surfaces - Yang Cheng; Zhiwei Yang; Xiaodan Gou; Qing Yang; Zichen Zhang; Shiyu Cui; Yuhua Ren; Lihong Fan; Haifeng Zhang; Zheng Fang; Yu Lu; Lin Kai; et al. (Chemical Engineering Journal, 2023)

Insight into the selective oxidation behavior of organic pollutants via Ni-N4-C mediated electron transfer pathway - Huchuan Yan; Cui Lai; Shiyu Liu; Dongbo Wang; Xuerong Zhou; Mingming Zhang; Ling Li; Dengsheng Ma; Fuhang Xu; Xiuqin Huo; Lin Tang; Ming Yan; et al. (Chemical Engineering Journal, 2023)

Population Pharmacokinetics and Pharmacogenetics Analyses of Dasatinib in Chinese Patients with Chronic Myeloid Leukemia - Shiyu He; Jinxia Zhao; Jialu Bian; Yinyu Zhao; Yuanyuan Li; Nan Guo; Lei Hu; Boyu Liu; Qianhang Shao; Huan He; Lin Huang; Qian Jiang (Pharmaceutical Research, 2023)

Tuning the intrinsic catalytic sites of magnetite to concurrently enhance the reduction of H2O2 and O2: Mechanism analysis and application potential evaluation - Ling Li; Min Cheng; Eydhah Almatrafi; Lei Qin; Shiyu Liu; Huan Yi; Lu Yang; Zhexin Chen; Dengsheng Ma; Mingming Zhang; Xuerong Zhou; Fuhang Xu; et al. (Journal of Hazardous Materials, 2023)

An updated review on chemical compositions, biological capabilities, and clinical benefits of cranberries - Naymul Karim; Ahmed K. Rashwan; Shiyu Liu; Jitbanjong Tangpong; Tao Lin; Wei Chen (Food Bioscience, 2023)

Bio-based tannic acid as a raw material for membrane surface modification - Shiyu Zhou; Yang Qu; Bowen Yang; Qiang Zhang; Jin Wang; Yamei Lin; Zhong Chen; Guo-Ping Lu (Desalination, 2023)

Efficient and selective removal of Hg(II) from water using recyclable hierarchical MoS2/Fe3O4 nanocomposites - Shiyu Li; Lin Yang; Jialong Wu; Linlin Yao; Deming Han; Yong Liang; Yongguang Yin; Ligang Hu; Jianbo Shi; Guibin Jiang (Water Research, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Design of a highly efficient Cu-based catalyst with two functional areas: The role of Cu0 and oxygen vacancies in Fenton-like system - Cui Lai; Lu Yang; Ling Li; Dengsheng Ma; Min Cheng; Shiyu Liu; Mingming Zhang; Huchuan Yan; Chensi Tang; Zhexin Chen; Lin Tang (Chemical Engineering Journal, 2023)

Rapid degradation of PFOA by the activated peroxymono-sulfate with FeCo/MoS2 catalyst - Yuancai Lv; Shiyu He; Shuting Liu; Zhendong Yu; Yanting Jiang; Yihui Hu; Yifan Liu; Chunxiang Lin; Xiaoxia Ye; Guifang Yang; Minghua Liu (Journal of Environmental Chemical Engineering, 2023)

Cold spells linked with respiratory disease hospitalization, length of hospital stay, and hospital expenses: Exploring cumulative and harvesting effects - Jin Feng; Dawei Cao; Dashan Zheng; Zhengmin (Min) Qian; Cunrui Huang; Huiqing Shen; Yi Liu; Qiyong Liu; Jimin Sun; Guangyuan Jiao; Xiaoran Yang; Stephen Edward McMillin; et al. (Science of The Total Environment, 2023)

Ambient air pollution associated with incidence and progression trajectory of cardiometabolic diseases: A multi-state analysis of a prospective cohort - Hongtao Zou; Shiyu Zhang; Miao Cai; Zhengmin (Min) Qian; Zilong Zhang; Lan Chen; Xiaojie Wang; Lauren D. Arnold; Steven W. Howard; Haitao Li; Hualiang Lin (Science of The Total Environment, 2023)

Alleviation of hypoxia stress induced oxidative damage, endoplasmic reticulum stress (ERS) and autophagy in grass carp (Ctenopharyngodon idellu) by TTO (Melaleuca alternifolia essential oil) - Ruoying Hu; Shiyu Wang; Lin Feng; Weidan Jiang; Pei Wu; Yang Liu; Xiaowan Jin; Shengyao Kuang; Ling Tang; Lu Zhang; Xiaoqiu Zhou (Aquaculture, 2023)

Short-term ambient particulate matter pollution of different sizes and respiratory hospital admission in the Beibu Gulf area of Southern China - Haopeng Li; Lizhong Liang; Shiyu Zhang; Zhengmin (Min) Qian; Miao Cai; Xiaojie Wang; Stephen Edward McMillin; Amy E. Keith; Jing Wei; Yan Geng; Hualiang Lin (Atmospheric Environment, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

Ambient particulate matter pollution of different sizes associated with recurrent stroke hospitalization in China: A cohort study of 1.07 million stroke patients - Miao Cai; Xiaojun Lin; Xiaojie Wang; Shiyu Zhang; Zhengmin (Min) Qian; Stephen Edward McMillin; Hannah E. Aaron; Hualiang Lin; Jing Wei; Zilong Zhang; Jay Pan (Science of The Total Environment, 2023)

An S-scheme CdS/K2Ta2O6 heterojunction photocatalyst for production of H2O2 from water and air - Cui Lai; Mengyi Xu; Fuhang Xu; Bisheng Li; Dengsheng Ma; Yixia Li; Ling Li; Mingming Zhang; Danlian Huang; Lin Tang; Shiyu Liu; Huchuan Yan; et al. (Chemical Engineering Journal, 2023)

Size-specific particulate matter and outpatient visits for allergic conjunctivitis in children: a time-stratified case-crossover study in Guangzhou, China - Jin Zhou; Lijun Fan; Hualiang Lin; Dehui Zheng; Lihong Yang; Dan Zhuo; Jiayang Zhuoma; Huan Li; Shiyu Zhang; Zengliang Ruan (Environmental Science and Pollution Research, 2022)

Global burden of chronic obstructive pulmonary disease attributable to ambient particulate matter pollution and household air pollution from solid fuels from 1990 to 2019 - Yinglin Wu; Shiyu Zhang; Bingting Zhuo; Miao Cai; Zhengmin Min Qian; Michael G. Vaughn; Stephen Edward McMillin; Zilong Zhang; Hualiang Lin (Environmental Science and Pollution Research, 2022)

Kinetics and Size Effects on Adsorption of Cu(II), Cr(III), and Pb(II) Onto Polyethylene, Polypropylene, and Polyethylene Terephthalate Microplastic Particles - Xiaoxin Han; Shiyu Wang; Xue Yu; Rolf D. Vogt; Jianfeng Feng; Lifang Zhai; Weiqi Ma; Lin Zhu; Xueqiang Lu (Frontiers in Marine Science, 2021)
Due to its small size, large specific surface area and hydrophobicity, microplastics, and the adsorbed contaminants may together cause potential negative effects on ecosystems and human beings. In this study, kinetics and size effects on adsorption of Cu(II), Cr(III), and Pb(II) onto PE, PP and PET microplastic particles were explored. Results indicated that the PE and PET microplastics have the higher adsorption capacity for Cu(II), Cr(III), and Pb(II) than that for PP microplastic. The adsorption capacity was affected by microplastic types and metal species. Among the three metals, Pb(II) had the largest adsorption amount on microplastic particles, especially on PET particles. Moreover, the adsorption capacities of microplastics increase with the decrease of particle size. The metal adsorption capacity of <0.9 mm microplastics is greater than that of 0.9–2 mm and 2–5 mm microplastics. The size effect on metal adsorption was largest for PE microplastic. More attention should be paid in case of the coexistence of heavy metals and tiny PE and PET microplastics in the environment.

Development and characterization of SNP markers in many-lined sun skink (Eutropis multifasciata) from transcriptomic sequences - Youfu Lin; Zijin Qian; Shiyu Shen; Yicheng Huang; Yu Du; Hong Li; Lian Chen (Conservation Genetics Resources, 2021)

Different experiences of two PRRT2-associated self-limited familial infantile epilepsy - Qianlei Zhao; Zhenwei Liu; Ying Hu; Shiyu Fang; Feixia Zheng; Xiucui Li; Feng Li; Zhongdong Lin (Acta Neurologica Belgica, 2020)
To analyze the clinical characteristics and PRRT2 gene mutation of self-limited familial infantile epilepsy and evaluate the treatment responses of different antiepileptic drugs in self-limited familial infantile epilepsy. We reviewed the clinical feature and genetic mutation results and treatment responses of two sibling sisters. They were detected with the PRRT2 gene mutation through Sanger sequencing. Elder sister was treated with oxcarbazepine oral suspension, while younger sister was treated with levetiracetam oral solution. The two sibling sisters exhibited PRRT2 heterozygous mutation inherited from their mother in c.649dupC p.(Arg217fs). Oxcarbazepine oral suspension had an immediate effect on the elder sister who was treated with it. However, levetiracetam oral solution had no effect on younger sister even though the dose was increased, but she got seizure-free after turning to oxcarbazepine oral suspension. Oxcarbazepine, which plays the mechanism of the sodium channel blockers, has a more significant effect than levetiracetam, which has no mechanism of the sodium channel blockers in self-limited familial infantile epilepsy. The PRRT2 gene of infantile epileptic patients with a family history of infantile convulsions or paroxysmal kinesigenic dyskinesia(PKD) could be detected by sanger sequencing and a biomarker to select antiepileptic drugs which play the mechanism of the sodium channel blockers could be utilized.

AsA–GSH Cycle and Antioxidant Enzymes Play Important Roles in Cd Tolerance of Wheat - Shiyu Qin; Hongen Liu; Zhaojun Nie; Wei Gao; Chang Li; Yonghui Lin; Peng Zhao (Bulletin of Environmental Contamination and Toxicology, 2018)

Smad signal pathway regulates angiogenesis via endothelial cell in an adipose-derived stromal cell/endothelial cell co-culture, 3D gel model - Shiyu Lin; Jing Xie; Tao Gong; Sirong Shi; Tao Zhang; Na Fu; Yunfeng Lin (Molecular and Cellular Biochemistry, 2016)

Application of statistical design for the optimization of microbial community of synthetic domestic wastewater - Yuancai Chen; Che-Jen Lin; Gavin Jones; Shiyu Fu; Huaiyu Zhan (Biodegradation, 2011)